Hidrocondicionamento, secagem e armazenamento em sementes de Piptadenia moniliformis Benth - Oliveira, Jéssica Christie Dantas de (Universidade Federal Rural do Semi-Árido, 2019)
Piptadenia moniliformis Benth. better known as catanduva, presents slow and uneven germination due to seed dormancy. Thus, it is fundamental to use techniques that can improve the uniformity of germination, either for seedling production or for direct seeding. In this sense, the hydroconditioning consists of the controlled imbibition of the seeds directly in the water or in humid substrates, allowing the activation of the metabolic processes of the germination, without occurrence of emission of the primary root, contributing for a faster and uniform germination. However, to facilitate handling and prolong maintenance of viability during storage, it is necessary to carry out the dehydration of the seeds after conditioning, which can be either naturally or artificially. The objective of this study was to evaluate the effects of hydroconditioning and drying types on germination and vigor of catanduva seeds during storage. For this, a sample of catanduva seeds was used, whose initial moisture content was determined by the oven method at 105 ° C for 24 hours with two replicates of 25 seeds. Then, the soaking curve was performed to determine the hydrocondensation time. For the preparation of the soaking curve and definition of hydrocondensation time, two subsamples of 25 were placed between two sheets of germitest paper at 25 ° C and weighed every one hour, until the radicle emission in 50% of the seeds. Thus, the time chosen for the hydroconditioning of the seeds was of 36 hours, when they reached 41,6% of humidity. After the hydroconditioning, a part of the seeds were submitted to natural drying in laboratory bench (average temperature of the environment 30 ° C) and the other one was submitted to artificial drying in forced air circulation (average temperature of 40 ° C for 24 hours ) until reaching the initial moisture level. Non- hydroconditioning seeds, hydroconditioning + natural drying and hydroconditioning + artificial drying without storage were submitted to the following evaluations: germination tests and accelerated aging in the laboratory, emergency, emergency speed index, root and shoot length, mass dry of the root and aerial part in greenhouse. The other seeds were stored in plastic bags in controlled chamber and the evaluations after 30 and 60 days of storage. The experimental design was completely randomized in a 3x3 factorial scheme, with three types of seeds (non- hydroconditioning, hydroconditioning + natural drying and hydroconditioning + artificial drying) and three storage periods (0, 30 and 60 days). It was verified that the hydrocondicionamento followed by natural or artificial drying, favors the vigor of catanduva seeds during 60 days of storage.
Monografia
Keywords: Condicionamento fisiológico; Germinação e vigor; Fabaceae; Catanduva; Physiological conditioning; Germination and vigor; Fabaceae; Catanduva; CIENCIAS AGRARIAS::AGRONOMIA